Peranan Fruktosa, Rafinosa, dan Trehalosa pada Kriopreservasi Semen Kuda - R I Arifiantini; B Purwantara; T L Yusuf; D Sajuthi (Faculty of Animal Science, Bogor Agricultural University, 2009)
The objective of this study was to evaluate the effectiveness of carbohydrates supplementation on the stallion semen cryopreservation. Semen was collected from 3 stallions using artificial vagina twice a week. Collected semen was evaluated macro-and microscopically. Semen showed >60% progressive motility was then divided into 3 tubes and diluted with skim milk 1:1, centrifuged at 1006 g for 10 minutes. Supernatan was removed and each pellet rediluted either with skim milk extender supplemented with 50 mM trehalose (ST); 50 mM raffinose (SR) or 100 mM fructose (SF) with the concentration of sperm were 200x106 ml-1. Extended semen packed into minitub 0.3 ml and equilibrates at 4 oC for 2 hours, freezes in the liquid nitrogen vapor for 10 minutes and stored in liquid nitrogen container -196 oC for further evaluation. After 24 hours, the semen was thawed at 37 oC for 30 second. The results of this experiment indicated that trehalose supplementation in skim milk was found to significantly improve the percentage of sperm motility (P<0.05) for stallion 1 and 3 compared to raffinose and fructose. But in all stallions, trehalose and fructose were superior compared to raffinose.Key words: Cryopreservation; stallion sperm; sugar